The Volatility of Long-Term Bond Returns: Persistent Interest Shocks and Time-Varying Risk Premiums - Osterrieder, Daniela; Schotman, Peter C. (The Review of Economics and Statistics, 2017)
We develop an almost affine term-structure model with a closed-form solution for factor loadings in which the spot rate and the risk price are fractionally integrated processes with different integration orders. This model is used to explain two stylized facts. First, predictability of longterm excess bond returns requires sufficient volatility and persistence in the risk price. Second, the large volatility of long-term bond returns requires persistence in the spot rate. Decomposing long-term bond returns, we find that the expectations component from the level factor is more volatile than returns themselves and that the risk premium correlates negatively with level-factor innovations.